As dificuldades e queixas de professores alfabetizadores em tempos de formação continuada - Altobelli, Cecília Célis Alvim (2008)
This research aims to investigate the reason for the alphabetizing teacher s lack of satisfaction faced by the Continuity Training course as well as the reason for the inefficiency of those courses in promoting changes to the actual practice of those teachers. In this sense, it questions the out of the measure observed between the Continuity Training and the results in the classroom, where all the proposed actions do not happen. It also searches, in the deep essence of education, the way performed by the teachers, since their initial training until the actual moment. This work also highlights the Continuity Training, trying to identify how it is absorbed by the teachers and it also gives opportunity to the discussions between theory and practice, from the angle of the teachers actions towards the Continuity Training. Theoretical support essentially focuses on meaning, sense and, in a complementary side, the teacher s identity. Based on the interviews, this research identify categories related to the disturbing feeling involving the teacher s practice as a consequence of the Continuity Training programs, which were analyzed and discussed under the thoughts of the Ciampa, Nóvoa and others. This is a qualitative research, taking the interviews on a person-to-person basis to form the data collection. It aims to reveal the point of view of three teachers integrants of the Continuity Training Program for more than one decade, in order to identify possible obstacles, improvement and retrocession in their practice and the possibility of all this be related to the Continuity Training perceived. The interview analysis has revealed itself as a warning regarding those trainings which have not considered the wide process of giving a meaning to the experiences as well as the production of teacher s knowledge, and, therefore, not promoting the professional autonomy